The impact of eWOM on consumers’ purchase intention : the moderation role of products’ category - Ventura, Madalena Mauhin Trigueiros (2017)
Online content is becoming an increasingly important tool for consumers and marketeers relationship to grow closer and last-longing. Namely, eWOM, which derived from the need of sharing knowledge and information among consumers, allowed them to reach information perceived as more trustful and real. Nowadays, this type of communication is part of the purchasing process and has been proved to influence consumers’ buying decisions. Besides being perceived as consumer generated information, eWOM can also be managed by marketeers, aiming at influencing individuals to provide useful information, which ideally would be positive but can also be negative, and managing potential future customers’ expectations and needs. In addition, this research quantifies the purchase intention among different types of eWOM, namely by exposing different sources, valences and structures and evaluating the impact on consumers’ buying decisions within different products’ categories. Therefore, quantitative data was generated by an online questionnaire which presented the different illustrative scenarios for each of the four categories of products being tested: pricey tech electronics, high touch retail, household staples and no touch services. The conclusions obtained were mostly opposing to literature, which may be explained by the various range of eWOM limitations and characteristics, as lack of physical contact, but also, were helpful to perceive that its influence is not linear and that it could depend on the scenario and the circumstances in which the information was developed and shared.